The effects of training intervention on the prevention of knee joint injuries: a systematic review and meta-analysis - Zheng, Gangbin; Zeng, Sai; Li, Tiangeng; Guo, Liang; Li, Ling (Frontiers in Physiology, 2025)
ObjectiveTo evaluate the impact of neuromuscular, core strength, balance, and proprioceptive training on preventing knee injuries in young athletes, to identify optimal intervention characteristics.MethodsThis review followed the 2020 guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). A systematic search of English and Chinese literature in databases included PubMed, Web of Science, EBSCO, CNKI, and Wanfang, covering studies published from January 1, 2000, to 12 April 2024. Inclusion criteria targeted randomized controlled trials (RCTs) on training interventions aimed at knee injury prevention among young athletes. The analysis used a random-effects model to pool data from studies meeting our criteria, ensuring a comprehensive evaluation of intervention effectiveness.ResultsA total of 19 randomized controlled trials (RCTs) involving 28,176 subjects were included. The meta-analysis showed that training intervention programs reduced the risk of lower extremity knee injuries by 25% (RR = 0.75, 95% CI: 0.65–0.85). The most notable effects were observed in intervention with exercise duration of 5–15 min, frequencies of 4–5 times per week, and program lengths exceeding 26 weeks.ConclusionThe findings highlight the effectiveness of specific training interventions in reducing knee injury risk among athletes. These insights provide a clear framework for designing training routines that effectively prevent knee injuries.